Healthier Together: Co‐design of a culturally tailored childhood obesity community prevention program for Māori & Pacific Islander children and families. (14th December 2020) - Hardt, Jessica; Canfell, Oliver J.; Walker, Jacqueline L.; Webb, Kerri‐Lyn; Brignano, Sebastien; Peu, Tevita; Santos, Daphne; Kira, Kirstine; Littlewood, Robyn
Abstract: Issue addressed: Children of Māori & Pacific Islander descent living in Australia have a greater prevalence of overweight/obesity and an increased risk of adverse health outcomes. This study aimed to co‐design Healthier Together, a community‐based, childhood overweight/obesity prevention program tailored to Māori & Pacific Islander cultures. Methods: Co‐design involved a three‐phase, iterative, participatory and experience‐based process, guided by the Te Ara Tika: Guidelines for Māori Research Ethics to promote respect and equity. Following traditional oratory customs of Māori & Pacific Islander cultures, "talanoa" facilitated the collaborative program design with recruited Māori & Pacific Islander consumers, cultural advisors and health professionals. Co‐design formulated program objectives, session plans, resources and evaluation tools. Results: Co‐design developed a 9‐week community‐based childhood overweight/obesity prevention program providing culturally tailored education across four themes: (a) nutrition (b) physical activity (c) positive parenting practices (d) culture and health. Strong community engagement developed a program highly tailored to the local Māori & Pacific Islander population. Conclusions: Co‐design methodology promotes equity and inclusion of all stakeholders, acknowledges and caters to diversity and creates a medium for openness, respect and shared purpose. Community‐led participatory approaches are pivotal to engaging and empowering communities to successfully improve health behaviours, particularly in tackling childhood overweight/obesity. So what?: Healthier Together is culturally significant to ensure relevance, effectiveness and sustainability. It is relevant and potentially adaptable to other priority populations across Australia and globally. Ultimately, the delivery of culturally tailored health care will contribute to a reduction in the health inequity experienced amongst priority populations.